EFL students motivational currents during Extensive Reading Programs: A retrodictive qualitative modelling - Ista Maharsi; Sugirin Sugirin; Ashadi Ashadi (Studies in English Language and Education, 2024)
Motivation to read, the driving force to achieve ones reading goals, plays a significant role in language learning as it relates to reading engagement and achievement. Its presence is prominently necessary for a longer learning period. This article explores the features of nine pre-service students motivational currents and how their motivation changes throughout the task performance in Extensive Reading Programs (henceforth ERPs). Data were collected from diaries, and a retrodictive qualitative model was applied to recount the experiences of the student participants motivational currents following Drnyeis Directed Motivational Currents (DMC). Themes of diaries and interviews were generated following the Interpretative Phenomenological Analysis. The findings show that the features of DMC are salient and functioning throughout the students learning experiences and facilitate the construction of their future identity as readers. Four patterns of motivational currents during the students learning were a steady wave, slight wave, moderate wave, and great wave patterns. The variability and stability of task performance motivation indicate that students motivational trajectories are unique, conditional, and context-bound. Identifications of the sources of motivators and demotivators provide hints for designing more engaging classroom activities, enriching the task features, and sustaining students motivation. This study concludes with possible directions for future motivation research.